2017
DOI: 10.1128/mbio.00500-17
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Compensation of Fitness Costs Is a General Outcome for Antibiotic-Resistant Pseudomonas aeruginosa Mutants Overexpressing Efflux Pumps

Abstract: It is generally assumed that the acquisition of antibiotic resistance is associated with a fitness cost. We have shown that overexpression of the MexEF-OprN efflux pump does not decrease the fitness of a resistant Pseudomonas aeruginosa strain compared to its wild-type counterpart. This lack of fitness cost was associated with a metabolic rewiring that includes increased expression of the anaerobic nitrate respiratory chain when cells are growing under fully aerobic conditions. It was not clear whether this me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 62 publications
1
51
0
Order By: Relevance
“…mtrC LOF mutations are enriched in cervical isolates and an inactive form of the pump activator MtrA exhibits similar trends, supporting a model in which reduced or eliminated mtrCDE efflux pump expression contributes to adaptation to the female genital tract. We hypothesized that the mechanism by which this occurs is through increased cytoplasmic acidification in anaerobic conditions 41 and demonstrated that LOF mutations in farA , encoding a subunit of the other proton motive force-driven pump FarAB, were likewise enriched in cervical isolates. mtrC and farA LOF mutations primarily occurred in short homopolymeric sequences and thus may occur via phase variation at a frequency higher than baseline mutation rate, similar to other resistance suppressor mutations 53 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…mtrC LOF mutations are enriched in cervical isolates and an inactive form of the pump activator MtrA exhibits similar trends, supporting a model in which reduced or eliminated mtrCDE efflux pump expression contributes to adaptation to the female genital tract. We hypothesized that the mechanism by which this occurs is through increased cytoplasmic acidification in anaerobic conditions 41 and demonstrated that LOF mutations in farA , encoding a subunit of the other proton motive force-driven pump FarAB, were likewise enriched in cervical isolates. mtrC and farA LOF mutations primarily occurred in short homopolymeric sequences and thus may occur via phase variation at a frequency higher than baseline mutation rate, similar to other resistance suppressor mutations 53 .…”
Section: Discussionmentioning
confidence: 99%
“…The associations we observed in the mtrCDE regulon raised the question of the mechanism by which the cervical environment could select for pump downregulation. Recent work on Pseudomonas suggested one possible model: overexpression of homologous P. aeruginosa efflux pumps belonging to the same resistance/nodulation/cell division (RND) proton/substrate antiporter family as MtrCDE results in a fitness cost due to increased cytoplasmic acidification 41 . This fitness cost was only observed in anaerobic conditions, where aerobic respiration cannot be used to dissipate excess protons efficiently 41 .…”
Section: A Second Class Of Proton-dependent Efflux Pumps Appears To Cmentioning
confidence: 99%
See 1 more Smart Citation
“…From an evolutionary perspective, there is a particular focus on the effect of acquisition of antimicrobial resistance has on the fitness of bacteria with a view to suppress the development of resistance [3][4][5]. Much of this work relies on the development of resistance in the presence of subinhibitory concentrations of single, or combinations of, antimicrobials and investigators employ a range of different media for the generation of resistance [4,[6][7][8], and the subsequent assessment of fitness related to acquired antimicrobial resistance [9,10]. However, the media currently used to grow bacteria in vitro is not necessarily the most suitable substitute for the environment that the bacteria live in in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…The unregulated overexpression of an efflux system not only contributes to antibiotic resistance but may also have pleiotropic effects in the bacterial physiology. We have recently reported that overexpression of RND systems in P. aeruginosa leads to an excessive internalization of protons that acidify the cytoplasm, which causes a biological cost in absence of oxygen or nitrate, since both are necessary to compensate for the intracellular H + accumulation (31, 32). In addition to these non-specific effects, other effects might be due to the unregulated extrusion of intracellular compounds, some of which may be relevant for the ecological behaviour of P. aeruginosa (33).…”
Section: Introductionmentioning
confidence: 99%